Anxiety Stadium Of Women's Handball Athletes Of The Contingent Of Bengkulu Province In Preparation For The Match At Pon Xxi Aceh-Sumut - Ilahi, Bogy Restu; Raibowo, Septian (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to determine the anxiety stadium of female handball athletes from the Bengkulu Province contingent in preparation for the match at PON XXI Aceh-Sumut. This research uses qualitative research with an emphasis on case studies using data collection techniques in the form of interviews, questionnaires and documentation. The subjects of this research were 2 coaches, 2 assistant coaches, and 19 athletes. The object of this research was the anxiety stadium of female handball athletes from the Bengkulu Province contingent in preparation for the match at PON XXI Aceh-Sumut. The research instruments used were interview guidelines, questionnaires and photo guidelines. Based on validation results from experts, 93% and 94% were obtained in the "Very Feasible" category for distribution to respondents. Based on the calculation results of the questionnaire data processing that has been distributed, the overall results of the anxiety stadium of female handball athletes from the Bengkulu Province contingent were obtained with an average percentage of 58% in the "Medium" category. The anxiety stadium is based on factors, namely Intrinsic Factors at 54% in the "Low" category, and Extrinsic Factors at 58% in the medium category, with the highest anxiety-causing indicator being "Equipment and Facilities" with a percentage of 70% in the "High" category. So we can conclude that the overall stadium of anxiety for female handball athletes from the Bengkulu Province contingent in preparation for the match at PON XXI Aceh-Sumut is in the "Medium" category.